2018
DOI: 10.1002/jcp.27029
|View full text |Cite
|
Sign up to set email alerts
|

Demethoxycurcumin: A naturally occurring curcumin analogue with antitumor properties

Abstract: The eradication of cancer in a patient remains an elusive challenge despite advances in early detection and diagnosis, chemo- and immunotherapy, pinpoint radiation treatments, and expert surgical intervention. Although significant gains have been made in our understanding of cancer cell biology, a definite cure for most cancers does not exist at present. Thus, it is not surprising that the research and medical communities continue to explore the importance and therapeutic potential of natural products in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 126 publications
(204 reference statements)
2
25
0
Order By: Relevance
“…However, few of those clinical trials showed positive outcomes [7], mainly due to its low solubility and poor bioavailability (<1%) [8]. Demethoxycurcumin (DMC) and diphenyl difluoroketone (EF-24) are natural and synthetic CUR analogues, respectively, that display multiple potent bioactivities and increased bioavailability compared to CUR [9,10]. For example, EF-24 was reported to have higher oral bioavailability (60%) and to be much safer than a chemotherapeutic drug in mice [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few of those clinical trials showed positive outcomes [7], mainly due to its low solubility and poor bioavailability (<1%) [8]. Demethoxycurcumin (DMC) and diphenyl difluoroketone (EF-24) are natural and synthetic CUR analogues, respectively, that display multiple potent bioactivities and increased bioavailability compared to CUR [9,10]. For example, EF-24 was reported to have higher oral bioavailability (60%) and to be much safer than a chemotherapeutic drug in mice [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EF-24 exhibited a 10~20-fold lower 50% growth inhibitory concentration (IC 50 ) than CUR in various solid tumor cells including ovarian, cervical, lung, breast, and prostate cancer cells [13][14][15][16]. Although these two CUR analogues, EF-24 and DMC, were reported to inhibit the proliferation of various solid tumor cells in in vitro and in vivo models [9,10], the precise impacts of these analogues on non-solid tumors, particularly AML, are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would appear appropriate to investigate the therapeutic potential of DMC for adjunctive treatment of various diseases (R. Li et al, ; Quitschke, ). We have recently reviewed the promising antitumor effects of DMC that are, in some cases, even greater than those of curcumin (Hatamipour et al, ). Here, our aim was to review the biological and pharmacological activity of DMC relevant to the treatment of noncancerous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, CUR was also reported to act as an iron chelator to interfere with ferritin expression and induce the apoptosis of prostate cancer cells [51]. Furthermore, the in vivo anticancer activities of DMC have been documented in a xenograft brain tumor-bearing mice model [26], suggesting the expression level of heme in brain tumors might not effectively abrogate the anticancer effect of DMC. These results suggest that the anticancer efficacy of DMC in various cancers in vivo might be dependent on the different proportions of heme-derived free iron and DMC in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low oral bioavailability, the clinical use of CUR in cancer therapy is limited. Recently, accumulating evidence proved that the second most abundant active component of curcuminoids, DMC, is an more efficient and stable agent than CUR for cancer therapy [24][25][26]. Until now, the precise cellular mechanisms of DMC against OSCCs have not yet been fully clarified.…”
Section: Introductionmentioning
confidence: 99%